A new species of Alvinocaris (Crustacea: Decapoda: Caridea: Alvinocarididae) and a new record of A. muricola from methane seeps on the Blake Ridge Diapir, Northwestern Atlantic - Komai, T.; Shank, T. M.; van Dover, C. L. (Zootaxa, 2005)
Two species of the alvinocaridid shrimp genus Alvinocaris, A. methanophila n. sp. and A. muricola Williams, are reported from a cold seep site on the Blake Ridge Diapir, northwestern Atlantic, at a depth of 2155 m. Alvinocaris methanophila is described and illustrated on the basis of 33 adult specimens. It is most similar to the sympatrically found A. muricola Williams, but differs in the comparatively stout second segment of the antennular peduncle and smaller size at maturity in females. Available data suggest that A. muricola is rare at this site. Brief notes on habitat and distribution of the two species are provided.